Functional design and biomechanical evaluation of 3D printing PEEK flexible implant for chest wall reconstruction. (October 2022) - Kang, Jianfeng; Tian, Yucong; Zheng, Jibao; Lu, Di; Cai, Kaican; Wang, Ling; Li, Dichen
Highlights: A novel 3D printing flexible PEEK chest wall implant was designed. Flexible implant provides excellent stiffness and strength under the chest compression. The mechanical properties of complete flexible implant under the dynamic impact and fatigue testing were investigated. The flexible implant can effectively restore the respiratory function in vivo . Abstract: Background and objective: Rigid reconstruction of chest wall defect seriously affects the postoperative respiratory owing to neglecting the functional role of natural costal cartilage. In the study, a 3D printing PEEK flexible implant was developed to restore the deformation capability during breathing motion. Materials and methods: Bionic spring structures in different region of implant were designed by taking into consideration of the anatomical morphology and materials properties of costal cartilage. The biomechanical properties of the rigid and flexible implants under the chest compression were compared through the finite element analysis. Two kinds of chest wall implant samples were fabricated with fused deposition modeling (FDM) technology to evaluate experimentally the mechanical behaviors. Finally, the restoration ability of respiratory function from the flexible implant was investigated in vivo . Results: The flexible implant exhibited the similar stiffness to the natural thorax and satisfied the strength demand in the chest compression. The maximal impact force of flexible implant reached to 536 N. The fatigue failure of complete flexible implant was revealed from the initiation and propagation of interlaminar crack to the fracture in a zigzag manner. Animal experiments validated that the parameters characterizing respiratory could be recovered to the preoperative and normal state. Conclusions: In the study, the flexible implant provided these advantages for perfect replication of thoracic shape, reliable safety, and great deformation capability to response respiratory movement, which given a superior treatment for chest wall reconstruction. Graphical abstract: Image, graphical abstract